Case Report: A Rare Condition of Abdominal Pain: Chemotherapy Induced Portal Vein Pneumatosis Mimicking the Bowel Necrosis - Chen, Chong-Cheng; Chen, Yi; Zhang, Yue-Xin; Chen, Ze-Hua; Yang, Kun (Frontiers in Surgery, 2021)
Portal vein pneumatosis is presence of air in the portal venous system, which is one of the classic radiologic features of bowel ischemia or necrosis. However, there are several other morbidities that can have portal vein pneumatosis as a complication. A case of 44-year-old man who suffered from severe abdominal pain after chemotherapy for soft tissue sarcoma of his left hip. The physical signs, laboratory findings, as well as the portal venous pneumatosis sign of CT scan strongly indicated the probability of bowel necrosis and subjected the treatment decision of patients to laparotomy finally. However, nothing abnormal except a segment of swollen small intestine was detected. Cautious should be kept in mind when encountering a patient with suspected bowel necrosis following chemotherapy since several chemotherapeutic agents could cause portal vein pneumatosis. Diagnostic laparoscopy might be a better option for such cases.